2001
DOI: 10.1021/jo010274k
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Homolytic Substitution at Selenium:  Synthesis of Novel Selenium-Containing Vitamin E Analogues

Abstract: Treatment of 1-(benzylselenenyl)-5-butyl-5-nonanol (10) with oxalyl chloride followed by the sodium salt of N-hydroxypyridine-2-thione afforded the corresponding pyridine-2-thione-N-oxycarbonyl (PTOC) oxalate ester which was not isolated but immediately heated to provide 2,2-dibutylselenane (7). This transformation presumably involves a tertiary alkyl radical that undergoes intramolecular homolytic substitution at selenium with loss of the benzyl radical to provide the selenium-containing ring system (7). A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…Yet, among all the available radical processes, intramolecular homolytic substitutions [2,3] have remained much less exploited than cyclization reactions, despite their strong synthetic potential. One solution to access these reactions is to use heteroatoms such as oxygen, [4] selenium, [5][6][7] phosphorus, [8,9] or silicon. [10,11] Sulfur is particularly wellsuited, and several reactions have been reported that employ homolytic substitution on this particular atom.…”
mentioning
confidence: 99%
“…Yet, among all the available radical processes, intramolecular homolytic substitutions [2,3] have remained much less exploited than cyclization reactions, despite their strong synthetic potential. One solution to access these reactions is to use heteroatoms such as oxygen, [4] selenium, [5][6][7] phosphorus, [8,9] or silicon. [10,11] Sulfur is particularly wellsuited, and several reactions have been reported that employ homolytic substitution on this particular atom.…”
mentioning
confidence: 99%
“…We attribute this observation to the electrophilicity of the pyridine ring in the various substrates, specifically that the electron-withdrawing ester substituent is able to increase ring reactivity in a manner that the alcohol can not. The alcohol 13 was further reacted with methanesulfonyl chloride to give the chloride 14 in 92% yield, which was subsequently reacted with t-butyl acetoacetate and base to give the ketoester 15 following the procedure developed by Malmström [13]. Treatment of 15 with concentrated hydrochloric afforded the required ketone 16 in excellent overall yield.…”
Section: Resultsmentioning
confidence: 99%
“…Water-soluble Vitamin E analogues that have been prepared include Trolox (6) [12], while our group has used intramolecular homolytic substitution chemistry to prepare a selenium containing analogue 7 of Vitamin E that possesses dual mode of action [13]. Work in our laboratories has also been directed at the development of water-soluble, dual acting, tocopherol/ebselen hybrids such as 8 and to pyridine-fused tocopherol systems such as 9.…”
mentioning
confidence: 99%
“…In order to develop novel antioxidants better than vitamin E, several efforts have been made to synthesize vitamin E analogues. [28][29][30][31][32][33][34][35][36][37] In this article, the possible ways for increase the antioxidant properties of vitamin E have been investigated with density function theory. Generally, there are three ways to develop novel antioxidants better than vitamin E: (1) the replacement of methyl groups by electron donating and electron withdrawing groups, (2) the replacement of oxygen heteroatom with other atoms and (3) reducing the number of atoms in the heterocyclic ring.…”
Section: Roomentioning
confidence: 99%